2018
DOI: 10.1017/s000305541800062x
|View full text |Cite
|
Sign up to set email alerts
|

Legislative Review and Party Differentiation in Coalition Governments

Abstract: Multiparty governance requires compromise and this compromise can lead to electoral losses. I argue that coalition members are motivated to differentiate themselves from their cabinet partners to mitigate potential electoral losses resulting from voters perceiving them as not rigorously pursuing their core policy positions or not possessing strong polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…Conversely, Sagarzazu and Klüver (2017) showed that at the beginning and at the end of the term the strategy of differentiation between coalition partners predominates, while coalition compromise is more likely in the middle of the term. As coalition participation influences voters' perceptions of partisan policy positions (Fortunato, Silva, and Williams 2018;Fortunato and Stevenson 2013), coalition members have incentives to differentiate themselves from their coalition partners to improve their electoral chances (Fortunato 2019).…”
Section: The Temporal Dimension Of Coalition Policy Making In Parliamentary Democraciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Sagarzazu and Klüver (2017) showed that at the beginning and at the end of the term the strategy of differentiation between coalition partners predominates, while coalition compromise is more likely in the middle of the term. As coalition participation influences voters' perceptions of partisan policy positions (Fortunato, Silva, and Williams 2018;Fortunato and Stevenson 2013), coalition members have incentives to differentiate themselves from their coalition partners to improve their electoral chances (Fortunato 2019).…”
Section: The Temporal Dimension Of Coalition Policy Making In Parliamentary Democraciesmentioning
confidence: 99%
“…Parliamentary institutions thus offer an imperfect mechanism for coalition partners to control ministerial discretion (Goodhart 2013). Empirically, it is difficult (if not impossible) to provide evidence for the level of imperfection as the coalition partner or opposition parties can also use parliamentary institutions to scrutinize and amend government bills (Fortunato 2019). Yet, the conventional wisdom and empirical evidence of government policy making are that the amount of parliamentary scrutiny increases with the level of policy divergence within coalition governments (Martin and Vanberg 2014;2020a;Pedrazzani and Zucchini 2013).…”
Section: The Temporal Dimension Of Coalition Policy Making In Parliamentary Democraciesmentioning
confidence: 99%
“…The key independent variable is majority party control and the dependent variable measures roll-call voting. The second type examines individual legislators as the unit of analysis with correlations between majority party status and legislator-level outcomes like roll-call votes (Crespin et al 2015;Curry and Lee 2019;Fortunato 2019). Both types carefully connect theory to empirics, but any findings have been correlative despite the causal claims implied by the theories tested.…”
Section: Does Majority Party Control Matter In the Us Senate? Scholars Are Dividedmentioning
confidence: 99%
“…One of the most important and outstanding questions in legislative politics is whether majority party control affects legislator behavior and agenda control. Since at least the 1970s, political parties successfully set the agenda on the US House floor (Cox and McCubbins 2005;Rohde and Aldrich 2010) and in multiparty democracies (Fortunato 2019;McElroy and Benoit 2012;Yoshinaka, McElroy, and Bowler 2010); though see Krehbiel (1998) for an alternative view. 1 The majority party's agenda setting in the US Senate, however, with its emphasis on individual power (Oppenheimer, Box-Steffensmeier, and Canon 2002;Reynolds 2017;Schiller 1995), is alleged to be much weaker (Curry and Lee 2019;Den Hartog and Monroe 2019).…”
mentioning
confidence: 99%
“…On one hand, they must come to an agreement and cooperate with their partners on a common agenda. To maintain support, on the other hand, they must convince supporters that they are not overly accommodating and that they represent their interests effectively (Fortunato 2019;Martin and Vanberg 2011). As a result, the types of bargains elites will agree to depend partly on their expectations of how those bargains will be evaluated by their supporters.…”
Section: Coalition Bargaining and Supporter Evaluationsmentioning
confidence: 99%